Making renewable energy investments sustainable through grid-connected solar pumps in Bangladesh - Mitra, Archisman; Mukherji, Aditi (International Water Management Institute, 2022)
The Bangladesh government plans to generate 10% of its electricity from renewable sources by 2030. The Infrastructure Development Company Limited (IDCOL), a nodal agency for renewable energy in Bangladesh, has so far installed 1,523 off-grid solar irrigation pumps (SIPs) with 42.1 megawatts (MW) capacity through an innovative fee-for-service model. These pumps have a high panel-to-pump capacity ratio to meet irrigation demands during the peak irrigation season of summer boro paddy. However, beyond the boro season, irrigation demand is limited. Over reliance on one crop for revenue generation and low usage during the off-season affect the financial viability of SIP investments. Grid integration can offer a one-stop solution for increasing the capacity utilization of solar panels and helping the government meet its renewable energy targets by utilizing the existing solar infrastructure.